VD_FINDINFO HC / 2012 / 153 vom 1. Februar 2012 - VD Tribunal cantonal (2012)
RÉSILIATION ABUSIVE, PROLONGATION DU BAIL À LOYER | 2 CC, 4 CC, 271 CO, 272 CO, 272b al. 1 CO, 444 CPC, 445 CPC, 451 ch. 2 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 13 LTB, 405 al. 1 CPC (CH)